Hydrolysis of alpha-s2-casein in solution by chymosin, plasmin, trypsin, and Lactobacillus-proteinases - Pihlanto-Leppälä, Anne; Pahkala, Eero; Kahala, Minna; Antila, Veijo (Agricultural Research Centre of Finland, The Scientific Agricultural Society of Finland, The Finnish Society of Dairy Science, 1993)
Tässä tutkimuksessa selvitettiin alphas2-kaseiinin entsymaattista hydrolyysiä eristämällä ja identifioimalla vapautuvia peptidejä. Entsyymeinä käytettiin kymosiinia, plasmiinia, trypsiiniä sekä kolmesta Lactobacillus helveticus- ja yhdeksästä Lactobacillus casei-kannasta eristettyä preparaattia. Kymosiinilla oli heikko proteolyyttinen aktiivisuus hydrolysoida käytettyä substraattia. Plasmiini vapautti käytetyissä olosuhteissa lukuisia peptidejä. Suurin osa identifioiduista fragmenteista vapautui C-terminaalista. Trypsiini hydrolysoi useita as2-kaseiinin sidoksia. Peptidejä vapautui lähes koko aminohappoketjun matkalta. Trypsiinin vaikutus kohdistui arginiinin ja lysiinin karboksyylipäihin. Laktobasillien proteolyyttinen vaikutus oli vähäistä.

The aim of this study was to examine the enzymic hydrolysis of alphas2-casein by isolating and identifying the released peptides. The enzymes applied in the study were chymosin, plasmin and trypsin as well as cell free extracts from three strains of Lactobacillus helveticus and nine strains of L. casei. The findings showed that chymosin had weak proteolytic activity on alphas2-casein. Plasmin, on the other hand, released numerous peptides under the used conditions. The majority of the identified fragments were released from the C terminal end of the substrate. Plasmin hydrolysed mainly Lys-X bonds. The third enzyme, trypsin, hydrolysed several bonds of as2-casein. Peptides were released from almost all regions of the protein. Trypsin acted on the carboxyl sides of arginyl and lysyl residues. Cell free extract of lactobacilli had little activity on alphas2-casein.
Keywords: Ta; peptidit; alphas2-casein; enzymatic hydrpöysis; peptides